Analisis Pengenalan Flora Dan Fauna Melalui Pembelajaran Tari Pada Kelas IV Di SD 5 Klaling - Farhana Nur Azura; Fadila Clara Solfiana; Viva Kafita; Rina Dwi Puspitasari (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This article aims to describe the process of learning dance with the theme of imitating Flora and Fauna through dance movements. By using a qualitative approach, this research explores more deeply how dance can grow students' self-confidence. This includes growing feelings of pride, having a brave nature, being able to control emotions, and developing more imagination and creativity. The methods used in this research are observation, interviews and documentation. This research also explores how dance can be an effective tool in education. The research results show that dance can increase students' creativity and skills. Students' perceptions of learning dance with the theme of imitating Flora and Fauna in class IV SD 5 Klaling are positive. Students feel happy, interested and enthusiastic in participating in dance learning. Thus, this research shows that learning dance forms positive characters in students, such as self-confidence, responsibility, cooperation and concern for the environment.